Environmental education instructional unit for junior high school grades - Hagen, Lois J. (My University, 1979)
The purpose of this project was: 1. ...to develop a unit of instructional materials related to environmental education. 2. ...to construct or select activities that are especially appropriate for junior high school-age students. 3. ...to include a variety of learning experiences in the program, including laboratory exercises and outdoor activities which could provide students with first-hand experiences in issues related to their environment. 4. ...to employ a wide range of instructional media such as motion pictures, filmstrips, cassette tapes, and other audio-visual instructional aids. 5. ...to implement the program as a six-week course of study. The activities developed in this project were designed to be used by an eighth grade class of students enrolled in the Westby (Wisconsin) Area School District. The unit of materials contains 27 individual learning activities and involves a six-week period of instruction. The program focuses on issues related to environmental deterioration. Air, land, and water pollution problems are the major topics of concern.
Keywords: Ecology -- Study and teaching (Secondary) -- Wisconsin -- Westby.; Environmental protection -- Study and teaching (Secondary) -- Wisconsin -- Westby.